CONSIDERATION OF ECONOMICAL PROBLEM IN RUSSIAN PHILOSOPHY FROM MORAL POINT OF VIEW AT THE TURN OF XXth CENTURY - O. A. Volnyakova (Российский технологический журнал)
The problem of correlation between economics and morality is risen in the article. Start of discussion of this problem from philosophical point of view dates from to the turn of XXth century and connected to the names of Russian religious thinkers V.S. Solovyov and S.N. Bulgakov. On the wave of tremendous development of economical theories of XIX century in the spirit of economism one-sided approach to human economical activity was found out in them. Chapters from the book of Russian philosopher V.S. Solovyov "Explanation of kindness" in which he considers economical question from moral point of view are analyzed in the article and S.N. Bulgakov's approach to rendering of political economy is shown. Critics of break of human economical activity and his moral substance is researched in details. Special attention is paid to consideration of human economic relations (work, property, exchange) in their correlation with morality from Solovyov's philosophy of unitotality. The fact that work has dual nature in society is shown : on the one hand it is necessary for satisfying human exigencies, on the other hand it must be directed to commonwealth, in such combination of egoism and altruism the way to building just society is paved. Views of philosopher to the fact that the source of property is work and exchange mustn't become a deceit are notched. The main philosophical conclusion is in the necessity of understanding of dialectical connection of material, economical and moral sides of human activity. The importance and actuality of given problem is shown.